From Post-Maoism to Post-Marxism : the Erosion of Official Ideology in Deng's China - Misra, Kalpana (Routledge, 1998)
This text chronicles Deng Xiaoping's institution of far-reaching and practical economic reforms that seem at odds with Communist theory and its emphasis on ideology. In fact, while Deng often turned to Mao for ideological justification of his reforms, those very reforms seemed to wear away to official ideology. Ultimately, even though the post-Mao.